Surface Waves New Trends and Developments - Ebrahimi, Farzad (IntechOpen, 2018)
Surface waves have drawn a significant attention and interest in the recent years in a broad range of commercial applications, while their commercial developments have been supported by fundamental and applied research studies. This book is a result of contributions of experts from international scientific community working in different aspects of surface waves and reports on the state-of-the-art research and development findings on this topic through original and innovative research studies. It contains up-to-date publications of leading experts, and the edition is intended to furnish valuable recent information to the professionals involved in surface wave analysis and applications. The text is addressed not only to researchers but also to professional engineers, students, and other experts in various disciplines, both academic and industrial, seeking to gain a better understanding of what has been done in the field recently and what kind of open problems are in this area.